Comparison of Subfoveal Choroidal Thickness Values with Severity of Diabetic Retinopathy in Type 2 Diabetes Mellitus Patients - Sandiyanto; Weni Helvinda; Kemala Sayuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Changes in choroidal thickness may be associated with increased severity of diabetic retinopathy and may occur simultaneously or even earlier than diabetic retinopathy. This study aims to compare the value of subfoveal choroidal thickness (SCT) with the severity of RD in patients with type 2 DM without RD with NPDR at Dr. M. Djamil General Hospital Padang, Indonesia. Methods: This research is a cross-sectional analytic observational study. The study was conducted on 36 eyes obtained from 29 study subjects. Data analysis was performed with the help of SPSS to determine the ratio of SCT thickness in diabetic retinopathy patients, p<0.05. Results: The thickest mean SCT value was found in the type 2 DM group without RD (328.78 + 14.78 mm) and the thinnest in the severe NPDR group (234,22 + 12,30 mm). Conclusion: The more severe the severity of diabetic retinopathy, the thinner the SCT (subfoveal choroidal thickness).